ANALYSIS OF EXISTING RISKS AND METHODS OF COMBATING THEM IN CLOUD TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2023)
This article provides an analysis of current threats and mechanisms in cloud technologies. In addition, clouds name, computer systems, all of the computers within the same network, are analyzed in clouds to display information within it. Each computer is not considered as an independent unit, but a whole system. In general, the user is provided directly to work directly to work. All network resources available through servers are illuminated.Modern information technologies often play a major role in the success of all areas. There are a number of means and options that allow us to use full power of cloudy technologies. The concept of cloudy technologies is really important because it can become a turn point of doing business and take it to a completely new level. This means that it can bring income not only for businesses, but also for the state.